A Prospective, Observational Study on Adverse Drug Reactions in Hospitalized Pediatric Cancer Patients in a Tertiary Care Teaching Hospital - Nancy Khajuria; Nikhil Menia; Seema Gupta (Journal of Pharmacy and Bioallied Sciences)
Background: Adverse drug reactions (ADRs) pose a major health concern worldwide, especially in paediatric oncology where unlicensed or off-label drugs are commonly used. These reactions can have a significant impact on the quality of treatment and the safety of patients, particularly in vulnerable paediatric populations. Aims and Objectives: The purpose of this study is to examine the occurrence and characteristics of chemotherapy-related adverse drug reactions in children with cancer at a teaching hospital specialising in advanced medical care. Furthermore, it aims to evaluate the intensity and cause of these reactions by utilising the NARANJO probability scale and other assessment instruments. Materials and Methods: During a three-month period, we conducted a study at SMGS Jammu, in collaboration with GMC Jammu’s Pharmacology Department. The study was observational in nature and followed a prospective approach. The study included 45 children undergoing chemotherapy, utilising both spontaneous and intensive monitoring systems to report and analyse adverse drug reactions. We conducted statistical analysis using Chi-Square and Fisher Exact tests. Results: Among the 45 patients included in the study, 20 individuals (44.44%) experienced adverse drug reactions (ADRs), with a higher prevalence observed among female patients (55%). Fever and vomiting were the most common adverse drug reactions observed, with most of them being classified as moderate in severity based on the Modified Hartwig and Siegel Scale. Commonly linked medications to adverse drug reactions include Methotrexate, Vincristine, L-asparaginase, and Cytarabine. There was no significant statistical link discovered between different categories of anticancer drugs and adverse drug reactions. Conclusion: this study highlights the prevalence of adverse drug reactions (ADRs) in children undergoing chemotherapy, particularly in those receiving treatment for acute lymphoblastic leukaemia. The findings emphasise the significant impact of ADRs on these patients. It is of utmost importance to closely monitor and manage adverse drug reactions (ADRs) in paediatric oncology, emphasising the importance of implementing improved drug safety measures.